Neuronal effects of ocean acidification in gilthead seabream (Sparus aurata) - Wang, Wenjing (2019)
As atmospheric CO2 increases, so does the amount of CO2 dissolved in the ocean; this causes ocean acidification. The impact of ocean acidification on marine biodiversity and ecosystems has received considerable attention; however, study of its effects on fish physiology and behaviour is just beginning. Although there is evidence that the atmospheric CO2 concentrations predicted to occur by the end of this century have mal-adaptive effects on olfactory-mediated behaviour of reef fish, the cellular mechanism(s) involved is unclear. In the current study, we recorded the olfactory responses of gilthead seabream (Sparus aurata) to explore the effects of high pCO2 and low pH – separately - on olfactory sensitivity. Exposure to elevated pCO2 (but at normal pH) significantly decreased olfactory sensitivity to some odorants, such as L-serine, L-leucine and L-arginine. Moreover, low pH (but at normal pCO2) also decreased olfactory sensitivity to L-serine, L-leucine and L-arginine and L-glutamine. At the histological level, medium-term exposure to ocean acidificaiton increased the ratio between non-sensory epithelium/total length of the lamella significantly at one week, three weeks and four weeks. Furthermore, the number of mucous cells increased significantly after four weeks of exposure to high pCO2 water. These structural changes suggest that the olfactory epithelium can respond to the changes in low pH and/or high CO2 levels, but cannot fully counteract the effects of acidification on olfactory sensitivity. Together, these results show that both high pCO2 and low pH can independently reduce olfactory sensitivity in marine fish, and that although acidification can evoke structural changes in the olfactory epithelium, these changes cannot fully restore olfactory sensitivity. Desde a revolução industrial que as atividades antropogénicas, como a utilização de combustíveis fósseis, liberta grandes quantidades de dióxido de carbono (CO2) para a atmosfera, levando ao aumento substancial da pressão de CO2 atmosférico ...